Lessons in Theory of Change from the Introductory Training on Theories of Change, Impact Pathways and Monitoring & Evaluation - Álvarez, S.; Jost, Christine; Schuetz, Tonya; Förch, Wiebke; Schubert, Cecilia; Kristjanson, Patricia M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) is using theory of change (TOC) planning to specify research outputs, the partnerships needed to produce the outputs, and a plausible hypothesis on how these outputs will contribute to CCAFS and CGIAR development outcomes. This brief reports back from the first training workshop with the team on developing TOCs, Impact Pathways and Monitoring and Evaluation.